The potential of utilising carbon dioxide-enhanced oil recovery coupled with carbon capture and sequestration in Trinidad and Tobago - Ramoutar, Kendal; Alexander, David; Bahaw, Edward; Boodlal, Donnie; Maharaj, Rean (Universiti Teknologi MARA, Sarawak, 2025)
On a worldwide scale, Trinidad and Tobago (T&T) produces less than 1% of global greenhouse gas (GHG) emissions, with the largest emissions stemming from its power generation, transportation, and industrial sectors. The EOR 26 reservoir was modelled using the Computer Modelling Group (CMG) software. Comparing the original oil in place (OOIP) from the IMEX model (1.83 MMSTB) to the actual OOIP (1.87 MMSTB) gave only a 0.04 MMSTB difference, which was close enough to match the model, injection and production data. The CMOST program in CMG was used to identify the parameters that significantly affected the model (using the Sobol Analysis). Simulations were conducted for each scenario, and a comprehensive data analysis and economic evaluation were conducted. Scenario 4 was the most favourable since it runs for 69 years (as opposed to 100 years), sequesters the most volume of CO2 (85.6 MtCO2), produces the most oil volume (1.4 mmbbls) and gives a positive NCF for a range of oil price sensitivities. The NPV of this project at a 15% discount rate was calculated to be 0.23 MMUSD and the payback period was less than 2 years. The economic evaluations can be improved by aligning costs and revenue closer to the T&T framework.